Genetic Association of UGT1A1 Promoter Variants (c.-3279T>G and c.-3156G>A) with Neonatal Hyperbili-rubinemia in an Iranian Population - Nasim Pouralizadeh; Gholamali Mamouri; Abbas Boskabadi; Hassan Boskabadi; Houshang Rafatpanah; Ali Moradi; Hassan Mehrad-Majd (Mashhad University of Medical Sciences, 2021)
Background: Several studies have reported that two promoter variants (c.-3279T>G and c.-3156G>A) in UDP-glucuronosyltransferase (UGT1A1) gene may contribute to neonatal hyperbilirubinemia. However, these variants have not been investigated in Iranian neonates. This cross-sectional study aimed to determine if the UGT1A1 promoter variants are significant risk factors associated with neonatal hyperbilirubinemia. Methods: A total of 178 unrelated neonates, including newborns with neonatal jaundice (n=95) and healthy controls (n=83), were included in this study. Each individual was genotyped by the PCR-RFLP and COP-PCR at nucleotides -3279 and -3156, respectively, using fresh blood DNA. Logistic regression analyses were performed to assess the association of UGT1A1 promoter variants with the presence of significant hyperbilirubinemia. Anthropometric indices and clinical variables were also compared between the different genotype groups. Results: Allele and genotype analysis of the c.-3279T>G and c.-3156G>A variants showed no significant association with the risk of neonatal hyperbilirubinemia neither in the crude nor after adjustment for gestational age, gender, and birth weight in different genetic models (P>0.05). However, in haplotype-association analysis, only one haplotype (A-T) was found to be associated with the risk of neonatal hyperbilirubinemia (OR=0.19, 95% CI; [0.18-0.20], P=0.001). Conclusion: This study failed to demonstrate that c.-3279T>G and c.-3156G>A variants alone might contribute to the risk of neonatal hyperbilirubinemia in Iranian neonates. However, the A-T haplotype may play a significant role in increasing the risk of hyperbilirubinemia.